2023
DOI: 10.1111/isj.12437
|View full text |Cite
|
Sign up to set email alerts
|

The importance of theory at the Information Systems Journal

Abstract: Information Systems Journal | BACKGROUND AND MOTIVATIONTheory is a crucial aspect of the information systems (IS) discipline. Authors draw from articles on how to develop theory and from the theories themselves to anchor knowledge contributions. Editors and reviewers expect to see novel theoretical insights in conjunction with empirical rigour and sophistication (cf. Hardin et al., 2022). The thinking of PhD students is shaped by discussions on the importance of theory through formal coursework and research se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Theory plays a crucial role in research, as it possesses the capacity to consolidate current knowledge, explain observed events and relationships, and forecast the emergence of unobserved events and relationships by relying on the explanatory principles embedded within the theory (Collins & Stockton, 2018;Kumasi et al, 2013;Levine & Markowitz, 2023). In fact, the significance of theory is underscored by certain journals (e.g., Wiley), which exhibit a preference for articles that offer substantial theoretical contributions (Díaz Andrade et al, 2023). Although scholars have recognized the importance of applying theories in research, it is undeniable that there is a scarcity of explicit theories in the field of LIS as evidence from research (Hjørland, 2000;Lor, 2014;Roy & Mukhopadhyay, 2023) indicates.…”
Section: Related Literaturementioning
confidence: 99%
“…Theory plays a crucial role in research, as it possesses the capacity to consolidate current knowledge, explain observed events and relationships, and forecast the emergence of unobserved events and relationships by relying on the explanatory principles embedded within the theory (Collins & Stockton, 2018;Kumasi et al, 2013;Levine & Markowitz, 2023). In fact, the significance of theory is underscored by certain journals (e.g., Wiley), which exhibit a preference for articles that offer substantial theoretical contributions (Díaz Andrade et al, 2023). Although scholars have recognized the importance of applying theories in research, it is undeniable that there is a scarcity of explicit theories in the field of LIS as evidence from research (Hjørland, 2000;Lor, 2014;Roy & Mukhopadhyay, 2023) indicates.…”
Section: Related Literaturementioning
confidence: 99%
“…However, virtual team studies relying on collective-level efficacy concepts that neglect the role of collaborative technologies renders research in this area tangentially sociotechnical and encumbers an essential stream of IS scholarship. Thus, to further advance it as a technology-focused conceptualization of collective-level efficacy explicitly developed for virtual team research, we rely on a deductive theory-driven approach (Díaz Andrade et al, 2023) to propose and empirically evaluate a research model in which VTE acts on virtual team outcomes indirectly through virtual team trust and participants' perceptions of problems associated with the situational constraints of time, geographical separation, and cultural differences. Providing evidence of the essential theoretical connection between VTE and trust, social cognitive theory (SCT) propositions propose that collective-level efficacy beliefs influence the interpersonal aspects of teamwork (Bandura, 1997), and, relatedly, virtual team researchers have viewed trust in terms of 'interpersonal relations' (Jarvenpaa et al, 1998, p. 31).…”
Section: Introductionmentioning
confidence: 99%